Can Dexmedetomidine Improve Arterial Oxygenation and Intrapulmonary Shunt during One-lung Ventilation in Adults Undergoing Thoracic Surgery? A Meta-analysis of Randomized, Placebo-controlled Trials - Su-Qin Huang; Jian Zhang; Xiong-Xin Zhang; Lu Liu; Yang Yu; Xian-Hui Kang; Xiao-Min Wu; Sheng-Mei Zhu (Chinese Medical Journal, 2017)
Background: One-lung ventilation (OLV) is a common ventilation technology during thoracic surgery that can cause serious clinical problems. We aimed to conduct a meta-analysis to compare oxygenation and intrapulmonary shunt during OLV in adults undergoing thoracic surgery with dexmedetomidine (Dex) versus placebo to assess the influence and safety of using Dex. Methods: Randomized controlled trials comparing lung protection in patients who underwent thoracic surgery with Dex or a placebo were retrieved from PubMed, EMBASE, MEDLINE, Cochrane Library, and China CNKI database. The following information was extracted from the paper: arterial oxygen partial pressure (PaO2), PaO2/inspired oxygen concentration (PaO2/FiO2, oxygenation index [OI]), intrapulmonary shunt (calculated as Qs/Qt), mean arterial pressure (MAP), heart rate (HR), tumor necrosis factor-α (TNF-α), interleukin (IL)-6, superoxide dismutase (SOD), and malondialdehyde (MDA). Results: Fourteen randomized controlled trials were included containing a total of 625 patients. Compared with placebo group, Dex significantly increased PaO2/FiO2(standard mean difference [SMD] = 0.98, 95% confidence interval [CI] [0.72, 1.23], P < 0.00001). Besides, Qs/Qt (SMD= −1.22, 95% CI [−2.20, −0.23], P = 0.020), HR (SMD= −0.69, 95% CI [−1.20, 0.17], P = 0.009), MAP (SMD= −0.44, 95% CI [−0.84, 0.04], P = 0.030), the concentrations of TNF-α (SMD = −1.55, 95% CI [−2.16, −0.95], P <0.001), and IL-6 (SMD = −1.53, 95% CI [−2.37, −0.70], P = 0.0003) were decreased in the treated group, when compared to placebo group. No significant difference was found in MDA (SMD = −1.14, 95% CI [−3.48, 1.20], P = 0.340) and SOD (SMD = 0.41, 95% CI [−0.29, 1.10], P = 0.250) between the Dex group and the placebo group. Funnel plots did not detect any significant publication bias. Conclusions: Dex may improve OI and reduce intrapulmonary shunt during OLV in adults undergoing thoracic surgery. However, this conclusion might be weakened by the limited number of pooled studies and patients.